Thermoresponsive and Biodegradable Amphiphilic Block Copolymers with Pendant Functional Groups - Lee, Bo Keun; Noh, Jung Hyun; Park, Ji Hoon; Park, Seung Hun; Kim, Jae Ho; Oh, Se Heang; Kim, Moon Suk (Tissue Engineering and Regenerative Medicine, 2018)
BACKGROUND:: To develop the biodegradability and thermoresponsive hydrogel, in this work we designed a pendant-functionalized, thermoresponsive, amphiphilic block copolymer. METHODS:: Methoxy poly(ethylene glycol) (MPEG)-b-[poly(ε-caprolactone)-ran-poly(ε-caprolactone-3-one)-ran-polylactic acid] (MCL) and (MPEG-b-[PCL-ran-POD-ran-PLA]) [MCL-(CO)] block copolymers were prepared by ring-opening polymerization of ε-caprolactone, OD and lactide monomers. The subsequent derivatization of MCL-(CO) provided MPEG-b-[PCL-ran-poly(ε-caprolactone-3-COOH)-ran-PLA] [MCL-(COOH)] with COOH pendant groups and MPEG-b-[PCL-ran-poly(ε-caprolactone-3-NH2)-ran-PLA] [MCL-(NH2)] with NH2 pendant groups. RESULTS:: The measured segment ratios of MCL-(CO), MCL-(COOH), and MCL-(NH2) agreed well with the target ratios. The abundances of the COOH and NH2 groups in the MCL-(COOH) and MCL-(NH2) copolymers were determined by 1H- and 13C-nuclear magnetic resonance spectroscopy, and agreed well with the target abundances. MCL-(CO), MCL-(COOH), and MCL-(NH2) formed homogeneous, white, opaque emulsions at room temperature. Rheological analysis of the block copolymer suspensions indicated a solution-to-hydrogel phase transition as a function of temperature. The solution-to-hydrogel phase transitions and the biodegradation of MCL-(CO), MCL-(COOH), and MCL-(NH2) were affected by varying the type (ketone, COOH, or NH2) and abundance of the pendant groups. CONCLUSION:: MCL-(CO), MCL-(COOH), and MCL-(NH2) with ketone, COOH, and NH2 pendant groups showed solution-to-hydrogel phase transitions and biodegradation behaviors that depended on both the type and number of pendant groups.
Keywords: Amphiphilic block copolymers; Methoxypolyethylene glycol; Pendant functional group; Pendant groups; Poly (epsiloncaprolactone); Rheological analysis; Thermo-responsive; Thermo-responsive hydrogels; Amphiphilic block copolymers; Biodegradation; Pendant group; Solution-to-hydrogel phase transitions; Thermoresponsive